Egg Production and Blood Lipid Profile Comparison Between Local Stock (Elba Chickens) and Commercial Stock (Hy-Line Brown) - Ismoyowati Ismoyowati; Setya Agus Santosa; Hermawan Setyo Widodo; Muhammad Yakubu Abare (Buletin Peternakan, 2026)
This study compared egg production and blood lipid profiles between local stock (Elba chicken) and commercial stock (Hy-line Brown) chicken. A total of 120 chickens (60 per group) were housed in individual battery cages under controlled conditions for eight weeks. Egg production data were collected daily, and blood samples were analyzed for lipid profiles at 28 weeks of age. Results showed significantly higher egg production in commercial chickens (52.57 ± 1.97 eggs) compared to local chickens (29.51 ± 8.36 eggs) (p < 0.001). Commercial chickens also demonstrated superior hen-day egg production (75.10 ± 2.81% vs 42.16 ± 11.94%, p < 0.001) and feed conversion ratio (2.13 ± 0.15 vs 2.85 ± 0.43, p < 0.001). Blood lipid analysis revealed significantly higher levels of cholesterol (120.38 ± 37.4 vs 98.84 ± 15.21 mg/dL, p = 0.02), triglycerides (213.55 ± 47.99 vs 100.23 ± 23.49 mg/dL, p < 0.001), and glucose (187.89 ± 30.79 vs 164.21 ± 21.13 mg/dL, p < 0.001) in local chickens compared to commercial chickens. A strong negative correlation was observed between egg production and triglyceride levels (r = -0.8368, p < 0.0001) across both populations. These findings demonstrate the effects of selective breeding on egg production efficiency and suggest potential differences in lipid metabolism between local and commercial chicken breeds.